Sulfated glycosaminoglycans from crown‐of‐thorns Acanthaster planci – extraction and quantification analysis. Issue 1 (14th December 2012) - Bahrom, Nur Afiqah; Sirajudeen, K. N. S.; Yip, George W.; Latiff, Aishah A.; Ghazali, Farid Che
Abstract In this article, the novel inventive steps for the extraction and quantification of sulfated glycosaminoglycan (GAG) from Acanthaster planci starfish, generally known as crown‐of‐thorns (COT), are reported. Starfish have been implicated with collagenous distributions within their body anatomy, thus making it a prima facie fact searching for the possibility that GAGs can be isolated from COT. In this study, total‐, N‐, and O‐sulfated GAGs were extracted from three anatomical regions of the COT (integument, internal tissue, and coelomic fluid) and comparison was made. The result showed that body region of COT seemed to contain higher amount of sulfated GAGs as opposed to the arm region (55.79 ± 0.65 μg/mg was the highest amount in the body extracted from its coelomic fluid and 32.28 ± 3.14 μg/mg was the highest amount in the arm extracted from its internal tissue). COT's integument and coelomic fluid from its body region possessed the highest total of sulfated GAGs content with no significant difference (P < 0.05) between the two. All GAGs from COT comprised a higher percentage of N‐sulfated GAGs than its counterpart, the O‐sulfated GAGs. When compared with a similar previous study that used sea cucumbers as the sulfated GAGs source, COT possessed more total sulfated GAGs content per milligram as compared with the sea cucumber generally. This result seems to unveil this marine species' advantage per se pertaining to GAGs extraction biomass applicability. Thus, COT could now be the better alternative source for production technology of total‐, N‐, and O‐sulfated GAGs.